2001
DOI: 10.1002/1097-4636(2001)58:1<47::aid-jbm70>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The use of dynamic mechanical analysis to assess the viscoelastic properties of human cortical bone

Abstract: The purpose of this study was to examine the use of a dynamic mechanical analyzer (DMA) system to study the viscoelastic nature of bone. Cortical bone specimens from human femora were tested isothermally for 150 min at 37 degrees C and the loss factor (tan delta) and storage modulus (E') were measured. To explore the effects of test conditions on tan delta and E', different levels of applied stress, two specimen sizes, and two hydration conditions (wet and vacuum-dried) were evaluated. Finally, nonisothermal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 26 publications
5
58
0
1
Order By: Relevance
“…This conclusion is consistent with the results of another study that showed the specimen-size effect on the storage modulus (Yamashita, 2001). Though DMA underestimated the values of elastic moduli, the anisotropic ratios for two directions for all positions were practically in the same range as those obtained from the quasi-static results -1.2 -1.8.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion is consistent with the results of another study that showed the specimen-size effect on the storage modulus (Yamashita, 2001). Though DMA underestimated the values of elastic moduli, the anisotropic ratios for two directions for all positions were practically in the same range as those obtained from the quasi-static results -1.2 -1.8.…”
Section: Discussionsupporting
confidence: 91%
“…To achieve those functions, the skeleton system should have adequate mechanical properties such as strength, stiffness, and fracture toughness (Yamashita et al, 2001). Due to age-based properties deterioration together with an increased fracture susceptibility as an outcome of structural changes, various experimental studies investigating the effect of structural properties of the cortical bone and its mechanical properties have been conducted (Zioupos and Curry, 1998;Zioupos et al, 1999;Wachter et al, 2002;Curry, 2004;Augat and Schorlemmer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The overall stress-strain trends of cortical bone measured in this study agree with bovine and equine studies in that the mechanical properties of the bone were anisotropic. Unfortunately, some investigators used dry bones for their studies, making it impractical to draw comparisons of the mechanical response to wet bones because of the significant effect of hydration of collagen on the mechanical behavior [14,15]. …”
Section: Comparison Of Cortical Bone Studiesmentioning
confidence: 99%
“…This drying process has been shown to alter the mechanical response of bone due to the hydration-dependent behavior of bone collagen [14,15]. Katsamanis et al [16] studied the effect of loading rate on the elastic modulus and Poisson's ratio of human femoral cortical bone using one-dimensional wave theory and strain gages bonded to the surface of the bone in two directions at multiple locations.…”
Section: Introductionmentioning
confidence: 99%
“…This observation clashes with the fact that M50 has high storage modulus. [338] (F n physiologica 02, [339,340] valu n tangent ma of the compo ure 7), [338] thu eeded for load that water ca cally bind the ave already s ains through th nic acid. [332] In ndence of me ticles also affe higher apatite line solution ( .…”
Section: Discussionmentioning
confidence: 99%